PRODUKSI BIOKOMPOSIT SEBAGAI DECORATIVE SHEET DARI ECENG GONDOK (EICHHORNIA CRASSIPES) DAN KAYU APU (PISTIA STRATIOTES) HASIL FITOREMEDIASI LIMBAH CAIR PABRIK TAHU - Yohana Panjaitan, Nora
Tofu wastewater contains a high enough amount of organic materials in it that can give negative impact for environment. Therefore, it is necessary to perform tofu wastewater treatment before it is discharged into the environment, one of which is through a phytoremediation process. Water hyacinth (Eichhornia crassipes) and water lettuce (Pistia stratiotes) are used as remediating agents because their ability to absorb contaminants in wastewater. In addition, both of these plants have a high cellulose content so that they can be used as a matrix reinforcement in the manufacture of biocomposites. The purpose of this study is to utilize fitoremedial biomass, E. crassipes and P. stratiotes to produce bio-product in the form of biocomposite as decorative sheet. Phytoremediation was carried out for 14 days with variations in waste concentration, namely 25% and 60% as well as controls originating from distilled water. Every two days data is collected for pH and TDS values, while other data collection, such as BOD, COD, TSS, NH3, NO2, and NO3 contained in wastewater and the wet weight of biomass is carried out on day 0 and day 14 of the phytoremediation processes. The study’s result indicate that the highest percentage reduction for all parameters analyzed in tofu liquid waste was found in the 60% waste variation, where the percentage reduction in the values of BOD (98%), COD (93%), TDS (89%), TSS (60%), NH3 (100%), NO2 (92%), dan NO3 (91%). Based on the wet weight of the biomass, the Relative Growth Rate (RGR) value of the plant is obtained as a growth parameter. E. crassipes (0.04 g.g-1.day-1) and P.stratiotes (0.03 g.g-1.day-1) had better retention in the tofu wastewater with a of 60% consent rate. This value also indicates that E. crassipes is a better remediator agent than P. stratiotes for tofu wastewater treatment. Biomass of E. crassipes and P. stratiotes resulting from phytoremediation of tofu wastewater at various concentrations of 60% waste which has better growth and percentage reduction in waste content is then used in the production of biocomposite. The resulting biocomposite was analyzed for density (0.89 g/cm3), absorption capacity (79.80%), and tensile strength (0.05 Mpa).